Antibiotic susceptibility of bacterial strains isolated from urinary tract infections inPakistan - Zahoor, Sarmad; Shehzad Ahmad, Naveed; Asif, Sadia; Muhammad Sajid Jehangir, Hafiz; Ali, Asad; Sohail Afzal, Muhammad; Mohsin Ali, Muhammad; Zahoor, Saroosh (International Journal of Medicine, 2021)
Background: Urinary track infection (UTI) is a common infection in Pakistan. Poor knowledge about personal hygiene and lack of awareness are major reasons of this infection. All over the world and in Pakistan E. coli and K. pneumonia are main causative agents of UTI.Objectives:To analyze Antibiotic susceptibility pattern of bacterial strains isolated from urinary tract infections.Methods: In present study total 227 samples from Genomic Research Lab and Diagnostic Center Rawalpindi, Pakistan were tested for presence of different microbial infectious agents and their antibiotic resistance and susceptibility pattern. Biochemical test such as Gram staining, Lactose fermentation test, Motility test, Catalase test and Colony formation on MacConkey agar, Indole test, and Citrate utilization test were applied. The antibiotic susceptibility and resistance pattern was evaluated by using fourteen different antibiotics on MullarHigton agar. Top ten antibiotics were selected at a cut off value of 100 samples for E. coli and 20 samples for Klebsiella.Results: Against E. coli and K. species the most susceptible antibiotic was Imipenam with 97.5% and Amikacin with 94.9% susceptibility respectively. Moreover, against E. coli and K. species the most resistance antibiotic was Ciprofloxacin 81.7% and Tobramycin with 76.1% resistance respectively. The comparison of present study with pervious studies had shown an increase in resistance against various antibiotics.Conclusion: It is concluded from the present study that antibiotic resistance is on raise in Pakistan and the effect of each antibiotic was different with respect to type of infectious agent so it is recommended that the doctor should determine the dominant type of infectious agent and its susceptibility response before prescription of any antibiotic.Â Â Â